2016
DOI: 10.1002/macp.201600210
|View full text |Cite
|
Sign up to set email alerts
|

Time and Temperature Evolution of the Rigid Amorphous Fraction and Differently Constrained Amorphous Fractions in PLLA

Abstract: In semi‐crystalline polymers, amorphous segments located in different regions and distance from the crystalline domains can exhibit different dynamics. In poly(l‐lactic acid) (PLLA), the existence of (i) two distinct mobile amorphous fractions (a completely mobile amorphous fraction and a slightly constrained mobile amorphous fraction), which vitrify/devitrify in the Tg region, and (ii) a rigid amorphous fraction, which vitrifies/devitrifies at temperatures higher than Tg, has been reported in the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 91 publications
3
48
0
Order By: Relevance
“…The crystallization process of polymers has been widely investigated by TMDSC [7,22,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. An accurate investigation of the crystallization process is a fundamental step for a full comprehension of the polymer structure, which in turn strongly influences the material properties.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization process of polymers has been widely investigated by TMDSC [7,22,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. An accurate investigation of the crystallization process is a fundamental step for a full comprehension of the polymer structure, which in turn strongly influences the material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the structural anisotropy induced in the liquid like-state plays no role on the apportionment of the different fractions. As observed by Righetti et al, [43,50] the establishment of the RAF depends on the crystallization temperature, i.e. on the molecular mobility of the polymer chains.…”
Section: Figmentioning
confidence: 69%
“…[47,48] RAF is commonly defined by opposition to the mobile amorphous fraction (MAF) in that its mobility is drastically restricted due to the geometrical constraints at the interface with the crystals. [49,50] Regarding the MAF, constrained and unconstrained MAF-depicted as intra-and interspherulitic amorphous phases respectively-have recently been reported for semicrystalline polyesters such as PET [51] and PLA. [43,52,53] Constrained and unconstrained MAF were revealed by differential scanning calorimetric measurements through the concept of cooperative rearranging regions (CRR) [54] as well as structural relaxation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This result is all the more surprising considering that the glass crystallization has yielded markedly less crystalline phase than crystallization from the melt. The complexity of the dynamics of the formation of the rigid amorphous phase has been revealed in studies by Righetti et al . The data on crystallization of poly[(R)‐3‐hydroxybutyrate] have demonstrated that under isothermal conditions at 30 °C, the rigid amorphous and crystalline phases develop in concert.…”
Section: Rigid Amorphous Phasementioning
confidence: 99%
“…to hypothesize that the rigid amorphous phase may play an important role in crystallization. A study of poly(lactic acid) has again demonstrated that the rigid amorphous phase continues to develop after the formation of the crystalline phase …”
Section: Rigid Amorphous Phasementioning
confidence: 99%